1998
DOI: 10.1111/1467-9280.00084
|View full text |Cite
|
Sign up to set email alerts
|

Limits to Infants' Knowledge of Objects: The Case of Magical Appearance

Abstract: Young infants have an impressive knowledge of material objects. They appreciate that distinct objects cannot occupy the same space at the same time, are internally cohesive units that maintain their boundaries, and exist continuously in space and time. We report a surprising limit to this body of understanding: Although 8-month-olds responded to the “magical” disappearance of an object as an unexpected event, they did not so respond to a magical appearance. These results suggest that infants' understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 20 publications
4
49
3
1
Order By: Relevance
“…Another experiment suggested infants may also have an implicit understanding of "precise" addition; specifically, that one item + one item = exactly two items. Wynn's (1992a) empirical results and the claim they provide evidence for arithmetical competencies in infancy have been the focus of intense scientific study and theoretical debate (Carey, 2002;Cohen, 2002;Cohen & Marks, 2002;Kobayashi, Hiraki, Mugitani, & Hasegawa, 2004;Koechlin, Dehaene, & Mehler, 1997;McCrink & Wynn, 2004;Simon, Hespos, & Rochat, 1995;Uller, Carey, Huntley-Fenner, & Klatt 1999;Wakeley, Rivera, & Langer, 2000;Wynn, 1995Wynn, , 2000Wynn, , 2002Wynn & Chiang, 1998). The findings for imprecise addition and (or) subtraction have been replicated several times (Cohen & Marks, 2002;Simon et al, 1995;Wynn & Chiang, 1998).…”
Section: Number and Arithmetic In Infancymentioning
confidence: 99%
“…Another experiment suggested infants may also have an implicit understanding of "precise" addition; specifically, that one item + one item = exactly two items. Wynn's (1992a) empirical results and the claim they provide evidence for arithmetical competencies in infancy have been the focus of intense scientific study and theoretical debate (Carey, 2002;Cohen, 2002;Cohen & Marks, 2002;Kobayashi, Hiraki, Mugitani, & Hasegawa, 2004;Koechlin, Dehaene, & Mehler, 1997;McCrink & Wynn, 2004;Simon, Hespos, & Rochat, 1995;Uller, Carey, Huntley-Fenner, & Klatt 1999;Wakeley, Rivera, & Langer, 2000;Wynn, 1995Wynn, , 2000Wynn, , 2002Wynn & Chiang, 1998). The findings for imprecise addition and (or) subtraction have been replicated several times (Cohen & Marks, 2002;Simon et al, 1995;Wynn & Chiang, 1998).…”
Section: Number and Arithmetic In Infancymentioning
confidence: 99%
“…2, 3). Wynn concluded that the infants were able to perform simple arithmetic calculations based on the assumption that infants look longer at unexpected events (4)(5)(6).…”
mentioning
confidence: 99%
“…Sixand 8-month-old infants seemingly cannot maintain the representation of a lack of an object measured with violation-of-expectation paradigms: while they see the unexpected or "magical" disappearance of an object as an unexpected event, they do not see the "magical" appearance of an object as an unexpected event (Kaufman, Csibra, & Johnson, 2003;Wynn & Chiang, 1998). On one hand, we can suppose that representing the lack of object is handled by the representation handling numerical information.…”
Section: Lack Of Developmental Models Of Understanding Zeromentioning
confidence: 98%
“…Overall, the results about whether ANS may represent zero are inconclusive. While some authors argue that ANS can store zero (Merritt & Brannon, 2013;Wynn & Chiang, 1998), these results can be debated, and according to some models it would be impossible to store zero by the ANS, because for example, the ANS might rely on perceptual properties, and missing stimuli (i.e., a non-symbolic empty set) cannot activate the appropriate features in the system (Dakin, Tibber, Greenwood, Kingdom, & Morgan, 2011). It is also possible that even if zero is stored by the ANS, it requires additional supporting processes.…”
Section: Lack Of Developmental Models Of Understanding Zeromentioning
confidence: 99%